2018
DOI: 10.1063/1.5044225
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable IR metamaterial with ultra-narrowband perfect absorption

Abstract: The integration of a high-performance metamaterial (MM) onto mechanically flexible and deformable substrates offers significant promise in flexible electronics. Here, we propose two types of stretchable infrared (IR) MMs to design a tunable perfect absorber with a ring-shape (PA-RS) and a cross-shape (PA-CS) on a PDMS/Au/PDMS substrate, respectively. By stretching devices along different directions, PA-RS and PA-CS exhibit ultra-narrowband, polarization-dependent/independent, and switchable characterizations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The permittivity and permeability of metamaterials can be tailored by properly engineering the geometrical dimensions and material compositions of their subwavelength periodic patterns. They are widely studied to realize thermal emitters and are perfect absorbers for energy harvesting, medical imaging, and high-sensitivity sensing applications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. By tailoring the geometrical dimensions, metamaterials can be designed to span broad operating wavelengths, including visible [31][32][33], IR [34][35][36][37][38][39], terahertz [40][41][42][43][44], and microwave light [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…The permittivity and permeability of metamaterials can be tailored by properly engineering the geometrical dimensions and material compositions of their subwavelength periodic patterns. They are widely studied to realize thermal emitters and are perfect absorbers for energy harvesting, medical imaging, and high-sensitivity sensing applications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. By tailoring the geometrical dimensions, metamaterials can be designed to span broad operating wavelengths, including visible [31][32][33], IR [34][35][36][37][38][39], terahertz [40][41][42][43][44], and microwave light [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–7 ] Many research efforts have been devoted to develop the high‐performance absorber with perfect absorption, [ 8 ] multi‐band absorption, [ 9,10 ] broadband absorption, [ 11 ] polarization‐independent absorption, [ 12 ] and omnidirectional incidence [ 13 ] spanned the entire spectrum. [ 14–17 ] To date, many tuning mechanisms are presented for tunable electromagnetic absorbers using coherent absorption, [ 18 ] semiconductor, [ 19 ] surface plasmon polariton, [ 20 ] and metamaterial. [ 2 ] Among them, metamaterial is an artificial structure composed of subwavelength unit cell, which exhibits extraordinary electromagnetic properties, such as negative refraction index, electromagnetic cloaking, perfect lensing, and perfect absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The classical design of a metamaterial is the configuration of a split-ring resonator (SRR). There has been much research presenting and demonstrating the use of diversified SRR designs [8][9][10][11][12][13], either symmetrically or asymmetrically, such as cross-shaped SRR [9], V-shaped SRR [10,11], spiral-shaped SRR [12], and multiple SRRs [13]. In view of these extraordinary optical properties of SRR-based metamaterials, there have been extensive studies reported in the different frequency ranges, from microwave, terahertz (THz), and infrared to visible spectra [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%